DAYA SAING KOMODITI RAMBUTAN DI KABUPATEN MINAHASA SELATAN - Liny J.N. Rasu; Grace A.J. Rumagit; Charles R. Ngangi; Yolanda P.I. Rori (COCOS, 2015)
ABSTRACT Liny Jecklien Novita Rasu. Competitiveness of Commodity Rambutan in South Minahasa District (under guidance of Grace AJ Rumagit as chairman, Charles R. Ngangi and Yolanda P. Rori as members). Â The objective to analyze the competitiveness of the commodity in the South Minahasa District. This research was conducted over two months from February to March 2015 in the Ongkaw Satu Village Sinonsayang Sub District, South Minahasa Regency. The data used are primary data and secondary data. Primary data collection was done by using a list of questions prepared in the form of a questionnaire, while the secondary data was taken from relevant institutions in this study such as the Department of Agriculture, Statistics, and BP3K. Sampling was simple random sampling. Samples were taken for one week of 15 people. The method of analysis used is Descriptive Analysis and Policy Analysis Matrix. The results of the research showed that the commodity rambutan in South Minahasa Regency competitiveness based on comparative advantage and competitive advantage with private profits calculation of 22,813,749 and 70,959,417 for the calculation of social benefits. Of the two indicators for competitiveness Private Cost Ratios indicate that commodity rambutan increasingly competitive with PCR <1 and Domestic Resource Cost Ratio indicates that commodity rambutan has a comparative advantage with DRCR <1.